2021
DOI: 10.18502/avr.v30i2.6100
|View full text |Cite
|
Sign up to set email alerts
|

Improve communication with deaf and hard of hearing clients during Covid-19

Abstract: The article's abstract is not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…A mixed‐methods online survey (3B) reported that patients felt communication with masks to be especially challenging in healthcare situations and that transparent masks may improve interactions (Saunders et al., 2021). Eleven non‐research articles (5A & 5B) also suggested benefits of using transparent masks in order to preserve facial expressions and allow for lip reading (Altschuler et al., 2021; Clancy, 2021; Dehkordi & Ghiyasvandian, 2021; Kilgore et al., 2021; Knollman‐Porter & Burshnic, 2020; McKee et al., 2020; Mehta et al., 2020; Mheidly et al., 2020; Mitchell & Hill, 2020; Murphy et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A mixed‐methods online survey (3B) reported that patients felt communication with masks to be especially challenging in healthcare situations and that transparent masks may improve interactions (Saunders et al., 2021). Eleven non‐research articles (5A & 5B) also suggested benefits of using transparent masks in order to preserve facial expressions and allow for lip reading (Altschuler et al., 2021; Clancy, 2021; Dehkordi & Ghiyasvandian, 2021; Kilgore et al., 2021; Knollman‐Porter & Burshnic, 2020; McKee et al., 2020; Mehta et al., 2020; Mheidly et al., 2020; Mitchell & Hill, 2020; Murphy et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Adults with normal hearing and adults with hearing impairments recommended assistive devices, including the use of transcription apps when communicating with facemasks (Saunders et al., 2021). The use of transcription apps that convert spoken words into written text in real‐time was also suggested by three non‐research articles (5B & 5A) (Carter, 2020; Dehkordi & Ghiyasvandian, 2021; Marler & Ditton, 2021; McKee et al., 2020), and general assistive technologies were suggested by an additional two non‐research articles (5B) (Houchens & Tipirneni, 2020; Mehta et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations